Metaphors of health and illness in the oral discourses of the indigenous Semai community in Perak, Malaysia - Lendik Edmond, Lisbeth Sinan (2017)
As the experience of health and illness and how it is expressed through language has been said to be influenced by cognitive processes as well as how the world is experienced, analysis of metaphors in language use has the potential to uncover insights into how specific discourse communities structure their perceptions and experiences about health and illness. This study sought to examine the use of metaphors of health and illness in the oral discourses of the Semai community, in order to understand the community’s sociopsychological construction of the phenomenon of health. In this study, semistructured interviews with members of the Semai community from a village in Perak were audio-recorded, transcribed, and analysed following the Pragglejaz Group’s Metaphor Identification Procedure (MIP) (2007). Analysis of the metaphors was informed by Lakoff and Johnson’s (1980) conceptual metaphor theory and Kövecses’ (2005) notion of metaphor variation. The result revealed that the participant’s construction of health and illness involves the conceptual mapping of embodied experience as well as socio-cultural elements in expressing abstract notions of health and illness. Based on the metaphors used by the participants in their stories, the dominant theme found was the orientation theme, such as HEALTH IS UP and, ILLNESS IS DOWN. More universal metaphors were found compared to culture specific ones which suggest that the participants shared general concepts relating to health experiences that have been identified in other populations. Findings from the study will contribute to better understanding about how people of the Semai community construct their experience of health and illness, an important consideration for health policy-makers that deal with the welfare of the Orang Asli.